DEGRADASI MORAL PADA PUISI “DEWA TELAH MATI” (Analisis Wacana Fungsional) - Sukarno Sukarno (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
This study aims to analyze a poem from linguistic framework. This is a library research, using qualitative data, documentary study, description, deconstruction and content analysis method. An intrinsic-objective approach is also employed in this research. The analysis commences from lexicogrammar which produces automatized pattern and non-automatized one. The automatized pattern produces the subject matter while the non-automatized pattern yields the first order of meaning. In addition, the first order of meaning serves as symbols to generate the second order of meaning or literary meaning. Finally, the literary meaning navigates us to generalize the deepest meaning of the poem. The research result proves that the subject matter of the poem is ‘the prostitute took the man and the hermit to the indecent swamp and killed them in the morning’. The first order of meaning of this poem refers to the clause six to ten. The literary meaning is ‘in immoral, wicked, and evil places, people do not believe in God anymore’. They do anything to get their ambition-such as wealth, rank, and women. Even, they are proud of their wealth, rank, and of showing their lust. Eventually, the deepest meaning of the poem is about ‘the moral degradation’.